Prekarno delo novinarjev kot grožnja svobodi izražanja - Čeferin, Rok (Javnost (Ljubljana), 2017)
The increase of flexible forms of employment relations is noticed in the Slovenian journalism. Frequently these forms are also precarious, which has or can have negative consequences for the quality of journalistic contents and imperils the watch-dog role of news media. The authors of this research paper substantiate the thesis that state authorities are responsible for the unclear legal position and generally unregulated precarious situation of journalists, which places pressure on journalists and as such represents a threat to freedom of expression. Analysis of the case-law of the European Court of Human Rights and the Constitutional Court of the Republic of Slovenia confirmed that state authorities must actively ensure conditions for the work of free media. If the state in its legislation permits precarious work of journalists, it breaches its positive obligations regarding the protection of freedom of expression, as it enables political and economic power to put journalists in a dependent position. Analysis of key documents showed that in Slovenia since 2002 different institutions (particularly journalistic organisations) have regularly called for improved regulation of the conditions. The state authorities have been acquainted with the issue and with the proposals for changing legislation, yet they have not regulated the problem of precarity in any aspect.
Keywords: novinarji; novinarstvo; pravna ureditev; prekarno delo; samozaposlovanje; svoboda izražanja